The Cambridge history of gay and lesbian literature - McCallum, E L, Ed; Tuhkanen, Mikko, Ed (Cambridge University Press, 2014)
"The Cambridge History of Gay and Lesbian Literature presents a global history of the field and is an unprecedented summation of critical knowledge on gay and lesbian literature that also addresses the impact of gay and lesbian literature on cognate fields such as comparative literature and postcolonial studies. Covering subjects from Sappho and the Greeks to queer modernism, diasporic literatures, and responses to the AIDS crisis, this volume is grounded in current scholarship. It presents new critical approaches to gay and lesbian literature that will serve the needs of students and specialists alike. Written by leading scholars in the field, The Cambridge History of Gay and Lesbian Literature will not only engage readers in contemporary debates but also serve as a definitive reference for gay and lesbian literature for years to come"--